Porcine Model of Anastomotic Stricture in Crohn's Disease - Lukas, Martin (Gastrointestinal endoscopy clinics of North America, 2022)
The development of new endoscopic methods is advancing rapidly. Current standard methods such as endoscopic balloon dilatation have only limited long-term effects. Surgery is more effective, but it also carries a higher risk of complications. Endoscopic stricturotomy and stricturoplasty are new methods expanding the range of possibilities of endoscopic treatment. These methods are advanced, technically demanding, and require adequate expertise and training. It is, therefore, necessary to have a tool for training and teaching these new methods. The live large animal model is a valuable tool in the development and testing of new, difficult, and dexterity intensive therapeutic methods thanks to its natural properties including bowel movements and tissue reactions such as swelling or bleeding. Animal model simulating secondary stricture in the site of the entero-colonic anastomosis has been created allowing not only to practice but also to develop new minimally invasive endoscopic techniques for the treatment of strictures in Crohn's disease (CD). High cost and stringent legislation represent the main limitations of more widespread use of large animal models in endoscopy.
Keywords: Animals; Dilatation; výsledek terapie; lidé; Constriction, Pathologic; prasata; Treatment Outcome; gastrointestinální endoskopie; Animal model; Stricture; retrospektivní studie; Crohn Disease; Endoscopy, Gastrointestinal; Swine; dilatace; Crohnova nemoc; Inflammatory bowel disease; zvířata; Retrospective Studies; stenóza; Humans